Liquid phase exfoliation of MoO2 nanosheets for lithium ion battery applications - Coleman, Jonathan; Nicolosi, Valeria; Boland, John (My University, 2019)
Molybdenum dioxide (MoO2) is a layered material which shows promise for a number of applications in the electrochemical energy storage arena. Mostly studied as a bulk layered material, MoO2 has not previously been exfoliated in large quantities. Here we demonstrate the liquid phase exfoliation of MoO2 in the solvent isopropanol, yielding reasonable amounts of good quality nanosheets. However, we found that, when dispersed in isopropanol under ambient conditions, MoO2 nanosheets are gradually oxidized to higher oxides such as MoO3 over a period of days. Conversely, if the nanosheets are processed into dried films immediately after exfoliation, and before oxidation has had a chance to progress, the nanosheets are relatively stable under ambient conditions, remaining unoxidised unless the films are heated. We also found that MoO2 nanosheets can be size selected by controlled centrifugation and show size-dependent optical properties. This allows us to propose spectroscopic metrics which allow concentration- and size-estimation from extinction spectra. Finally, we found that liquid-exfoliated MoO2 nanosheets could be used to produce lithium ion battery anodes with capacities of up to 1140 mA h g−1.
PUBLISHED
cited By 3
Keywords: Molybdenum dioxide (MoO2); Nanosheets; Lithium ion batteries